Prognostic evaluation of resectable colorectal cancer using platelet-associated indicators - Qian, Weihua (Oncol Lett, 2019)
Colorectal cancer (CRC) represents the third most common malignancy worldwide. The aim of the present study was to investigate the predictive values of platelet-associated indicators, including platelet count (PLT), plateletcrit (PCT), mean platelet volume (MPV) and platelet distribution width (PDW) in patients with resectable CRC. The current retrospective study included 153 patients who were pathologically diagnosed with resectable CRC. The patients were divided into two groups according to the median value of PLT, PCT, MPV or PDW. To evaluate the changes in PLT, PCT, MPV and PDW following resection and adjuvant chemotherapy, the concept of post-/pre-treatment PLT, PCT, MPV and PDW ratios was introduced, where <1 indicated decreased PLT, PCT, MPV and PDW values after treatment, and where ≥1 suggested stable or increased values. It was revealed that a low MPV prior to treatment correlated with a higher tumor stage. Surgery significantly decreased MPV, but had no impact on PLT, PCT or PDW. Adjuvant chemotherapy significantly decreased PLT and PCT, increased MPV and had no effect on PDW. After the whole course of treatment (surgery combined with adjuvant chemotherapy), PLT, PCT and PDW were significantly decreased. Kaplan-Meier plots illustrated that patients with a post-/pre-treatment MPV ratio <1 had poorer overall survival (OS), whereas the post-/pre-treatment ratios for PLT, PCT and PDW did not correlate with patient outcome. Multivariate Cox regression analysis revealed that sex, tumor size and the post-/pre-treatment MPV ratio were prognostic factors for OS. Therefore, the present results may suggest MPV as a potential prognostic factor in resectable CRC.